PENGARUH INDEKS PERSEPSI KORUPSI, PENGELUARAN PEMERINTAH DAN PENERIMAAN PAJAK TERHADAP PERTUMBUHAN EKONOMI ASEAN-5 TAHUN 2002-2011 - Rino Bagus Haryanto; Sa songko (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This paper is based on the empirical evidence on the effects of corruption on economic growth. There are two different opinions, some have argued that corruption can reduce economic growth and others argue corruption can increase economic growth. Based on empirical evidence to the contrary in various objects of research, the authors try to review and analyze how the effects of corruption on economic growth in ASEAN-5 countries consisting of Indonesia, Malaysia, Singapore, Thailand and the Philippines. ASEAN-5 is a region that describes the emerging economies. This paper uses panel data analysis of five countries during the period of 2002-2011. Keywords: Corruptions, ASEAN-5, Corruption Perceptions Index, Growth, Rent-seeking.